Gas chromatography-mass spectrometry characterization of bioactive compounds from Ziziphus nummularia (Burm. F.) stem bark with promising in vitro antiplasmodial activity - Babita Aggarwal; Pankaj Sharma; Hardarshan S Lamba (Wolters Kluwer Medknow Publications, 2020)
Objective: This study was carried out to evaluate the in vitro antiplasmodial activity of alcoholic and hydroalcoholic extract of Ziziphus nummularia stem bark as well as the determination of core structure fractionated from its crude extract. Materials and Methods: The antiplasmodial activity of stem bark extracts was investigated by in vitro schizont maturation inhibition assay against Plasmodium falciparum (both chloroquine sensitive and resistant). The crude extract was analyzed by gas chromatography-mass spectrophotometry (GC-MS). Result: Both alcoholic and hydroalcoholic extracts showed their potential toward in vitro antiplasmodial activity against P. falciparum strains MRC-02 (CQ sensitive) and RKL-09 (CQ resistant). Alcoholic extract showed more promising antiplasmodial activity with Inhibitory concentration (IC50) of 0.130 and 1.191 for MRC-02 and RKL-09 strains, respectively, as compared to hydroalcoholic extract with IC50 of 1.856 and 2.981 for MRC-02 and RKL-09 strains, respectively. No morphological changes in erythrocytes were observed when investigated for chemical injury to the erythrocytes. Chemical characterization of alcoholic extract was performed by GC-MS analysis to identify the bioactive compounds that are responsible for antiplasmodial activity. Alkyl esters, phenolics, and flavonoids were found as major compounds and also showed resemblance to existing antimalarial drugs. Conclusion: The findings suggested that the investigated extracts will provide a foundation for combating the resistant strains of P. falciparum. Also, the compounds isolated from Z. nummularia crude extract are viable newer chemical antimalarial candidates requiring further investigation.